Evaluation of prognostic value and stage migration effect using positive lymph node ratio in gastric cancer. Issue 1 (January 2017) - Komatsu, S.; Ichikawa, D.; Nishimura, M.; Kosuga, T.; Okamoto, K.; Konishi, H.; Shiozaki, A.; Fujiwara, H.; Otsuji, E.
Abstract: Aims: To detect the best cut-off value of the positive lymph node ratio (PLNR) for stratifying the prognosis and analyzing its value with regard to stage migration effect using PLNR in gastric cancer. Methods: We retrospectively analyzed 1069 consecutive gastric cancer patients, who underwent curative gastrectomy with radical lymphadenectomy from 1997 through 2009. Results: 1) The mean number of dissected lymph nodes was 42.6 in pStage I, 32.4 in pStage II and 37.1 in pStage III. The PLNR of 0.2 was proved to be the best cut-off value to stratify the prognosis of patients into two groups ( P  < 0.0001; PLNR <0.2 vs. PLNR ≥0.2), and patients were correctly classified into four groups: PLNR 0, PLNR 0–<0.2, PLNR 0.2–<0.4 and PLNR ≥0.4 by the Kaplan–Meier method. 2) Compared patients with the PLNR <0.2, those with the PLNR ≥0.2 had a significantly higher incidence of pT3 or greater, pN2 or greater, lymphatic invasion, vascular invasion and undifferentiated cancer. Multivariate analysis showed that the PLNR ≥0.2 was an independent prognostic factor [ P  < 0.0001, HR 2.77 (95% CI: 1.87–4.09)]. 2) The PLNR cut-off value of 0.2 could discriminate a stage migration effect in pN2–N3 and pStage II–III, which patients with PLNR ≥0.2 might be potentially diagnosed as a lower stage after gastrectomy. Conclusion: The PLNR contributes to evaluating prognosis and stage migration effect even in a single institute and enable to identify those who need meticulous treatments and follow-up in patients with gastric cancer.